2020
DOI: 10.1136/bmjgast-2020-000541
|View full text |Cite
|
Sign up to set email alerts
|

Life in lockdown: experiences of patients with IBD during COVID-19

Abstract: ObjectiveCOVID-19 has disrupted the normal way of life in the UK, but for some patients with inflammatory bowel disease (IBD), the impact of this unprecedented global emergency was far greater. We aimed to assess the experience of patients with IBD during the COVID-19 lockdown.DesignWe designed a survey focused on the impact of COVID-19 on IBD healthcare, social and psychological well-being and quality of life. To capture those most likely to be affected we targeted survey invitations at our British Society of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
44
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 12 publications
1
44
2
Order By: Relevance
“…As a result, the current survey achieved a relatively high response rate (61.9%) compared to previous studies. 4,5,26 In summary, most patients with IBD adhered strictly to the general principles for the prevention of epidemics. Although there were concerns about the increased risk of COVID-19 among IBD patients, most patients believed that maintaining their treatment is important.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the current survey achieved a relatively high response rate (61.9%) compared to previous studies. 4,5,26 In summary, most patients with IBD adhered strictly to the general principles for the prevention of epidemics. Although there were concerns about the increased risk of COVID-19 among IBD patients, most patients believed that maintaining their treatment is important.…”
Section: Discussionmentioning
confidence: 99%
“…24 25 29 The changed measures during the pandemic, described previously, come with uncertainty and stress, which could explain the low score of the emotional function and social function domains of the IBDQ in our study population. [30][31][32] Optimal IBD course consists of clinical symptoms combined with monitoring of biomarkers such as faecal calprotectin and C reactive protein. 13 33 34 However, during the pandemic, outpatient clinic visits were cancelled, resulting in reduced ability to collect blood for possible follow-up of biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…Higher stress levels associated with lockdown measures were observed in some groups, such as women [185][186][187] (particularly pregnant women 188,189 ), single/divorced adults 81 , older people (particularly with pre-existing mental health conditions 175,190 ), parents with young children 191 , university students and young adults [192][193][194] , workers 195 , those self-medicating 196 , the economically deprived 143 , those with pre-existing depression 197 , bipolar disorders 198 , and other chronic medical conditions 139,189,[199][200][201] . A large study of 56,679 participants in China found that quarantine had a profound effect on the mental health of specific vulnerable groups, including those with pre-existing mental disorders, chronic physical diseases, frontline workers, and those living in the most affected areas 202 .…”
Section: Stressmentioning
confidence: 99%